Activity-based Learning in Primary Classrooms Through the Lens of Philosophical Assumptions - Bajaj, Abhilasha (JOURNAL OF INDIAN EDUCATION, 2021)
It is often seen that children’s voices and experiences do not find expression in the existing subject-centred classrooms. Whenever they speak, they generally answer the questions being asked by the teacher. Most of the time the students simply repeat and rote memorise the prescribed course content. They have no active role to play in the teaching–learning process and they act as mute spectators. But considering the fact that children are active learners, we must encourage them to talk about what they are learning. At the same time, they should be able to relate it with their previous experiences. Critical thinking and reflections should be an integral part of their process of knowing. In classrooms, if we allow the students to choose a topic of their choice and learn how a thorough understanding of this topic can be applied to solve a practical problem, then their engagement level in the task will increase. Learners may have a deeper understanding of the topic and can assess their skills as well. This paper talks about the nature of active learning from the philosophical perspective of Dewey’s theory of progressive education, Vygotsky’s theory of social context, and the theory of constructivism. The theoretical framework has been substantiated by the examples explained in the boxes. These examples are based on the observations of teaching–earning practices in the classrooms of MCD Schools.